THE DIGITAL TRANSFORMATION OF SOCIETYAND THE CHALLENGES FOR INFORMATION SECURITY - Yordanova, Steliana; Garov, Stoyan (E-Journal VFU, 2024)
The digital transformation of society and the issues facing information security are becoming increasingly common challenges in today’s interconnected world. The presented article aims to fragmentarily examine in the historical context, the key "players", the impact and challenges of the digital transformation of society and in the context of information security. In addition, it identifies and analyzes the influence of certain individuals who have made significant contributions to the field. Different points of view are analyzed and discussed in the essay, and a reasoned synthesis of different scientific and practical points of view is realized. Both positive and negative aspects of the issue are covered and potential future developments related to the digital transformation of society and information security are considered.